Testing the moderating role of self-reliance and social support on the mediated relationship of help-seeking attitudes and behavior through intentions among individuals with mental health concerns - Bugtong, Mahjalin Araiza S. (Animo Repository, 2019)
Studies have shown that mental health problems have become a growing public health concern. Despite this, a gap still exists in those who need mental health services and those who seek professional help. Although there are many studies on help-seeking, only few have focused on thoroughly examining the strength of relationships among the elements of help-seeking, namely, attitudes, intentions, and actual behavior. To gain an improved understanding of what influences professional help-seeking for mental health concerns, the researcher extended the study by adding variables such as self-reliance and social support. The researcher examined if the indirect influence of attitudes toward help-seeking on actual help-seeking behavior through help-seeking intention varies at individual’s different levels of self-reliance and social support on a sample of 604 Filipino participants whose age ranged from 18 to 25 years. A moderated mediation analysis using Hayes’ Process Model 9 revealed that none of the investigated factors of help-seeking moderated the relationship between attitudes toward help-seeking and actual help-seeking behavior through help-seeking intention. Nevertheless, the study found that social support predicts actual help-seeking behavior through help-seeking intentions. Thus, an individual who has positive attitudes toward seeking professional help, and who perceives social support for these behaviors will likely seek professional mental help. As such, social support can serve as social encouragement along path-ways to mental health care.